2015
DOI: 10.1016/j.bpj.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Glucose-Induced cAMP Oscillations in Pancreatic β Cells: cAMP Rocks when Metabolism Rolls

Abstract: Recent advances in imaging technology have revealed oscillations of cyclic adenosine monophosphate (cAMP) in insulin-secreting cells. These oscillations may be in phase with cytosolic calcium oscillations or out of phase. cAMP oscillations have previously been modeled as driven by oscillations in calcium, based on the known dependence of the enzymes that generate cAMP (adenylyl cyclase) and degrade it (phosphodiesterase). However, cAMP oscillations have also been reported to occur in the absence of calcium osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…In particular, when the relative activity of PDE1 is greater than the activity of AC8, Ca 2+ -driven cAMP degradation dominates, resulting in an out-of-phase cAMP-Ca 2+ relationship. On the other hand, if the relative activity of AC8 is greater than that of PDE1, Ca 2+ -stimulated cAMP production is favored and an in-phase relationship is observed, consistent with previous modeling studies (Peercy et al 2015;Fridlyand et al 2007).…”
Section: Oscillatory Phase Is Regulated By Balanced Activities Of Ca supporting
confidence: 90%
“…In particular, when the relative activity of PDE1 is greater than the activity of AC8, Ca 2+ -driven cAMP degradation dominates, resulting in an out-of-phase cAMP-Ca 2+ relationship. On the other hand, if the relative activity of AC8 is greater than that of PDE1, Ca 2+ -stimulated cAMP production is favored and an in-phase relationship is observed, consistent with previous modeling studies (Peercy et al 2015;Fridlyand et al 2007).…”
Section: Oscillatory Phase Is Regulated By Balanced Activities Of Ca supporting
confidence: 90%
“…Also GLP‐1‐induced cAMP oscillations were in phase with those of [Ca 2+ ] i. The phase relationship is probably determined by the level of [Ca 2+ ] i together with the Ca 2+ sensitivity of the specific ACs and PDEs engaged by the stimulus, an assumption supported by mathematical modelling . However, the situation is probably even more complex because cAMP production is positively regulated also by cell metabolism, but ATP and Ca 2+ oscillations are synchronized in antiphase in β‐cells .…”
Section: Spatio‐temporal Aspects Of β‐Cell Camp Signallingmentioning
confidence: 86%
“…These isoforms are subject to multiple regulatory inputs but the stimulatory effect of glucose may simply reflect increased availability of ATP, the substrate for all ACs . However, since the ATP concentration is potentially saturating even under low glucose conditions, glucose may instead act via lowering of AMP to relieve its inhibitory effect on AC activity . As mentioned above, the soluble AC (sAC), has lower affinity for ATP and has been suggested to play a role in glucose sensing in INS‐1 cells and islets .…”
Section: Glucose‐induced Camp Signalling In β‐Cellsmentioning
confidence: 99%
“…Equations for the dynamics of cAMP were recently added to an earlier version of the DOM [ 44 ] and it was shown that this version was capable of producing cAMP oscillations in model β-cells. We employed these equations, where the cAMP concentration is determined by the difference between its production by adenylyl cyclase ( V AC ) and degradation by phosphodiesterases ( V PDE ): where, where c is the cytosolic free Ca 2+ concentration, which stimulates both AC and PDE.…”
Section: Methodsmentioning
confidence: 99%
“…Since PKA activity is cAMP-dependent, changes in the cAMP concentration in the β-cell can in principle regulate Kir2.1 channel activity. Recent studies employing FRET-based sensors and TIRF microscopy showed that glucose induces cAMP oscillations in mouse β-cells [ 42 , 43 ], which may be accounted for by oscillations in metabolism [ 44 ]. It is therefore possible that, in KO cells, metabolic oscillations drive cAMP oscillations which in turn drive oscillations in Kir2.1 current, and this replaces oscillations in K(ATP) current as the mechanism for bursting electrical activity.…”
Section: Introductionmentioning
confidence: 99%